Erythema Multiforme: A Review of Clinical Manifestations, Diagnosis, and Management - GÜNGÖR, TUĞÇE; TARÇIN, BİLGE; GÜMRÜ TARÇIN, BİRSAY (Platanus Publishing, 2023)
Erythema multiforme (EM) is an infrequent, acute, sometimes recurrent, typically self-limiting, immune-mediated vesiculobullous inflammatory and hypersensitivity reaction with varied aetiologies characterised by distinct acrally distributed target-like cutaneous eruptions with or without mucosal involvement (Scully & Bagan, 2008; Trayes, Love, & Studdiford, 2019). Although it was first described by Bateman (1817), the first characteristic morphological feature of this particular eruption along with its aetiology was defined by Ferdinand von Hebra (1866) with the term “erythema exudativum multiforme”. Afterwards, Thomas (1950) recommended that EM with the typical clinical picture with cutaneous involvement described by Hebra (1866) be named as “EM minor”, and variants with more severe mucocutaneous lesions as “EM major”. This chapter is aimed to comprehensively review the epidemiology, aetiology, classification, clinical manifestations, diagnosis, differential diagnosis, and management of EM to enable dentists, who may encounter cases of EM with significant oral involvement, become familiar with the clinical picture for prompt diagnosis and management or referral to a specialist for appropriate management.